Knowledge and Compliance of Mothers of Children Under 5 Years Regarding the Vaccination Schedule: San Expedito Settlement, Paraguay, 2024 - Portillo Villalba, Fidelina; Silva Estigarribia, Arturo; Romero Vallejos, Anyelo David; Rodríguez-Riveros, María Isabel (Medicina Clínica y Social, 2025)
Introduction: Vaccination schedules are evidence-based recommendations that allow populations to prevent communicable diseases in different age groups through immunization. Objective: To determine the knowledge and compliance with vaccination schedules among mothers of children under 5 years of age in the San Expedito settlement, San Lorenzo, Paraguay, 2024. Methodology: A descriptive, observational, non-experimental, quantitative study was conducted. The study population consisted of mothers of children under 5 years of age. The sample included 40 mothers selected through non-probabilistic sampling. Data were collected through interviews using a structured questionnaire. Information was tabulated in Microsoft Excel 2010 and analyzed with EpiInfo 7.2.0.1. Tables and descriptive graphs were generated. Results: Participants ranged in age from 18 to 36 years (mean 27). More than half of the children were infants. Half of the mothers had completed secondary education, a quarter were housewives, and over 10% worked as cashiers. More than half of the households reported incomes below the minimum wage. Regarding knowledge, more than half of the mothers lacked information about vaccination. However, more than half complied with the vaccination schedule according to the child’s age. Conclusion: Limited knowledge about vaccination was observed among mothers, although compliance with the vaccination schedule was above 50%. These findings highlight the need to strengthen education and awareness strategies in the community
Keywords: Schedule; vaccination; immunization; mothers; children